1958
DOI: 10.1111/j.1365-2621.1958.tb17588.x
|View full text |Cite
|
Sign up to set email alerts
|

Buckwheat as a Supplement to All‐vegetable Protein Diets

Abstract: Successful all-vegetable rations for poultry feeding employing locally available feedstuffs have been previously developed for use in Central America (6,7). With this experience and other studies of the value of plants which grow well in the area, INCAP Mixture 8 ( V M 8) a vegetable mixture for human consumption has been developed from local foods and tested (1,.5). This formula has been shown to be effective for the treatment, and suitable for the prevention, of a form of severe protein malnutrition in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1959
1959
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Feeding experiments of Sure (1955) have shown that the proteins in buckwheat are the best known source of high biological value proteins in the plant kingdom, having 92.3 % of the value of nonfat milk solids and 81.4% of whole egg solids. The proteins of buckwheat were shown to have excellent supplementary value to the cereal grains (Sure, 1955;Wyld et al, 1958). Sokolov and Semikhov (1968) fractionated proteins of diploid and tetraploid forms of buckwheat; globulins were a main component of both.…”
Section: Buckwheatmentioning
confidence: 99%
“…Feeding experiments of Sure (1955) have shown that the proteins in buckwheat are the best known source of high biological value proteins in the plant kingdom, having 92.3 % of the value of nonfat milk solids and 81.4% of whole egg solids. The proteins of buckwheat were shown to have excellent supplementary value to the cereal grains (Sure, 1955;Wyld et al, 1958). Sokolov and Semikhov (1968) fractionated proteins of diploid and tetraploid forms of buckwheat; globulins were a main component of both.…”
Section: Buckwheatmentioning
confidence: 99%
“…Sure (1955) reported, on the basis of studies with albino rats, that buckwheat provided the best source of high biological value proteins in the plant kingdom (92.3% of the value of dried non-fat milk solids and 81.4% of dried whole egg). Wyld et al (1958) reported that 3-day old chicks fed for 35 days rations in which buckwheat replaced 0, 33.3, 66.6 and 100% of the corn of all-vegetable protein diets, showed a significant linear response in growth and feed efficiency to increases in buckwheat in the diet. It was concluded that the ration with buckwheat supplied enough lysine since the addition to it of 0.4% lysine had no additional effect on growth.…”
Section: Introductionmentioning
confidence: 97%
“…Other raw materials of much potential are pseudocereal grains; among these grains, some attention was given to buckwheat (Fagopyrum trataricum) [42,43] and, more recently, grain amaranth [44][45][46]. Amaranth grain contains relatively high levels of protein with a good essential amino acid balance of lysine, methionine, and tryptophan [46].…”
Section: Further Exploration Of Locally Available Protein Sourcesmentioning
confidence: 99%
“…It also contains 6% to 10% oil, a higher level than in cereal grain. Amaranth improves the protein quality of cereal grains, oilseed flours, and grain legumes [43]. Mixtures of amaranth flour with milk (Amaralac) and with soybean flour have been developed [46].…”
Section: Further Exploration Of Locally Available Protein Sourcesmentioning
confidence: 99%
See 1 more Smart Citation